2006
DOI: 10.1124/jpet.106.103077
|View full text |Cite
|
Sign up to set email alerts
|

p53 Suppression of Arsenite-Induced Mitotic Catastrophe Is Mediated by p21CIP1/WAF1

Abstract: Arsenic trioxide, an acute promyelocytic leukemia chemotherapeutic, may be an efficacious treatment for other cancers. Understanding the mechanism as well as genetic and molecular characteristics associated with sensitivity to arsenite-induced cell death is key to providing effective chemotherapeutic usage of arsenite. Arsenite sensitivity correlates with deficient p53 pathways in multiple cell lines. The role of p53 in preventing arsenite-induced mitotic arrest-associated apoptosis (MAAA), a form of mitotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 34 publications
3
47
1
Order By: Relevance
“…Our previous studies and those of others have demonstrated that arsenite-induced apoptosis is associated with arrest in mitosis (States et al, 2002;Taylor et al, 2006;McCollum et al, 2003;Huang et al, 2000;Ling et al, 2002). Therefore, we examined cell cycle distribution with flow cytometry and mitotic index analysis.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our previous studies and those of others have demonstrated that arsenite-induced apoptosis is associated with arrest in mitosis (States et al, 2002;Taylor et al, 2006;McCollum et al, 2003;Huang et al, 2000;Ling et al, 2002). Therefore, we examined cell cycle distribution with flow cytometry and mitotic index analysis.…”
Section: Discussionmentioning
confidence: 92%
“…SK-Mel-3 cells treated with high concentrations of arsenite alone and at lower concentrations of arsenite in combination with either BSO or MK571 accumulated in the S-phase compartment ( Figure 6A). We previously observed an arsenite-induced accumulation of fibroblasts with Sphase DNA content that was subsequently found not to consist of S-phase cells but rather degenerating G 2 cells (Taylor, McNeely, Miller, Lehmann, McCabe, Jr., and States, 2006). To examine if a similar phenomenon was occurring in the SK-Mel-3 cells, cultures were treated for flow cytometric analysis as before with the exception that they were pulsed with 10 µM 5-bromo-2'-deoxyuridine (BrdU) for 1 h prior to harvest at 12 and 24 h to specifically label the S-phase cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitotic catastrophe (MC) has been reported as a prominent response to different anticancer drugs that affect cytoskeletal components and include microtubule toxins (Tounekti et al, 1993;Lock and Stribinskiene, 1996;Torres and Horwitz, 1998;Taylor et al, 2006), radiotherapy (Streffer et al, 1986;Falkvoll, 1990;Zolzer et al, 1995;Bhattathiri et al, 1998;Widel et al, 1999) and chemotherapy (Yashige et al, 1999). Cell cycle checkpoint inhibitors in combination with DNA-damaging agents enhance MC by inducing 'mitotic slippage'.…”
Section: Clinical Relevance Of Cell Death Pathwaysmentioning
confidence: 99%
“…For example, arsenic delays progression through each cell cycle phase, and also causes an arrest at the G 1 /S and G 2 /M transitions (McCabe, Jr. et al, 2000;McCollum et al, 2005;McNeely et al, 2006;Taylor et al, 2006). Furthermore, Suzuki and Tsukamoto (2006) demonstrated that acute arsenic exposure impaired the normal proliferative response in rat liver after partial hepatectomy.…”
Section: The Effect Of Arsenic and Lps On Indices Of Hepatocyte Divisionmentioning
confidence: 99%